(untitled) (Gaceta Técnica, 2024)
The United Nations Organization since 2015, the Sustainable Development Goals have been proposed for global management, and specifically in the construction sector corresponding to objective 11, professionals in the architecture, engineering and construction sector have a crucial role in this context, given that it is responsible for the design, construction and maintenance of the built environment, which implies a significant impact on several sustainability indicators. However, it faces complex challenges, especially in countries like Venezuela, where multidisciplinary problems make it hard to gain progress towards these objectives. But it should be noted that progress in the use of digitalization and implementation of innovative technologies are seen as key solutions to improve sustainability in these areas. The use of tools such as Building Information Modeling and Generative Design is presented as a strategy to optimize architectural and structural design, allowing better integration of sustainability from the initial stages of projects. In this document, approached as a documentary-type investigation, it is concluded that the combination of BIM and DG can facilitate the creation of more efficient and sustainable design solutions, aligned with the Sustainable Development Goals, thus promoting a more responsible and sustainable built environment